2022
DOI: 10.3390/brainsci12010078
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Exercise on fMRI of the Midbrain Ascending Arousal Network Nuclei in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) and Gulf War Illness (GWI) in a Model of Postexertional Malaise (PEM)

Abstract: Background: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS), Gulf War Illness (GWI) and control subjects underwent fMRI during difficult cognitive tests performed before and after submaximal exercise provocation (Washington 2020). Exercise caused increased activation in ME/CFS but decreased activation for GWI in the dorsal midbrain, left Rolandic operculum and right middle insula. Midbrain and isthmus nuclei participate in threat assessment, attention, cognition, mood, pain, sleep, and autonomic dy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
5
0
1
Order By: Relevance
“…While the study record on exercise effects in ME/CFS using blood analyses is heterogenous, the brain imaging results are more consistent. Indeed, all neuroimaging studies that have compared ME/CFS patients with healthy controls demonstrated abnormalities in response to cognitive ( Barnden et al, 2015 , 2016 ; Shan et al, 2016 , 2017 ; Washington et al, 2020 ) or physical exertion ( Baraniuk et al, 2021 ; Rayhan and Baraniuk, 2021 ). Some of these abnormalities were interpreted to indicate dysfunction of the glia-controlled neurovascular unit ( Staines et al, 2018 ; Shan et al, 2020 ; Nelson T. et al, 2021 ).…”
Section: The Case For Neuroglial Dysfunction In Myalgic Encephalomyel...mentioning
confidence: 99%
“…While the study record on exercise effects in ME/CFS using blood analyses is heterogenous, the brain imaging results are more consistent. Indeed, all neuroimaging studies that have compared ME/CFS patients with healthy controls demonstrated abnormalities in response to cognitive ( Barnden et al, 2015 , 2016 ; Shan et al, 2016 , 2017 ; Washington et al, 2020 ) or physical exertion ( Baraniuk et al, 2021 ; Rayhan and Baraniuk, 2021 ). Some of these abnormalities were interpreted to indicate dysfunction of the glia-controlled neurovascular unit ( Staines et al, 2018 ; Shan et al, 2020 ; Nelson T. et al, 2021 ).…”
Section: The Case For Neuroglial Dysfunction In Myalgic Encephalomyel...mentioning
confidence: 99%
“…Affection of vegetative hubs such as the hypothalamus and the hypothalamo-pituitary-adrenal axis is also frequently suggested to play a central role in the pathogenesis of fatigue 49 . With respect to the periaqueductal gray, increased activation has been measured after provocation of exercise in patients suffering from chronic fatigue syndrome 50 . In a cohort covering the late subacute phase (on average three months) after COVID-19 infection, an association between fatigue scores and lower fiber density within a widespread network of association, projection, and commissural tracts was detected 51 .…”
Section: Discussionmentioning
confidence: 99%
“…A weak response by the HPA axis could explain at least hypocortisolism and PEM symptoms [ 17 ]. Recent fMRI studies of patients with ME/CFS have indicated impairment of reciprocal connectivity among several brain regions including the hypothalamus [ 52 ], and exercise-mediated overactivation in the whole RN and midbrain [ 53 ]. Consistent with reports of a reduced salivary cortisol awakening response and reduced serum ACTH levels [ 54 ], we also observed significantly reduced serum levels of cortisol in seventeen patients with ME/CFS (Fig.…”
Section: Discussionmentioning
confidence: 99%